If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(1 + -1x) + x = -1(6 + -2x) + 6 (1 * -5 + -1x * -5) + x = -1(6 + -2x) + 6 (-5 + 5x) + x = -1(6 + -2x) + 6 Combine like terms: 5x + x = 6x -5 + 6x = -1(6 + -2x) + 6 -5 + 6x = (6 * -1 + -2x * -1) + 6 -5 + 6x = (-6 + 2x) + 6 Reorder the terms: -5 + 6x = -6 + 6 + 2x Combine like terms: -6 + 6 = 0 -5 + 6x = 0 + 2x -5 + 6x = 2x Solving -5 + 6x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -5 + 6x + -2x = 2x + -2x Combine like terms: 6x + -2x = 4x -5 + 4x = 2x + -2x Combine like terms: 2x + -2x = 0 -5 + 4x = 0 Add '5' to each side of the equation. -5 + 5 + 4x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 4x = 0 + 5 4x = 0 + 5 Combine like terms: 0 + 5 = 5 4x = 5 Divide each side by '4'. x = 1.25 Simplifying x = 1.25
| .375x+1.375=x-3 | | 30=2x(9+y) | | 2y^5=x+1 | | Y+3.5=15.3 | | 4x+37=9x-8 | | 3(x+2)-(y-2)=14 | | -3h-27=5-7h | | 19-4x=-41 | | 39y^12+9y^5= | | 23=4m+m+2 | | 3x^4+6x^3=9x^2 | | V-5=-4v+5 | | u^2-2uv-48v^2= | | 6y-7=5y-20 | | 4b-8-b=3b+2(3b-4) | | 15m-44=-7m | | 3=x+18 | | 8h-2-6h=16 | | 0.25(n+5)=10 | | 25-9y=16y | | 3x^4+6x^3=9x | | 3=x+139 | | c^2+5c-7= | | 5x+24=-3x | | 27a+24= | | -2x-8=-6x-4 | | 3x/2=(3x+3)/8 | | -16(2y+15)=-12(2y-10) | | -2x-8=-6-4 | | (x-3)(ax+4)=0 | | m*n-6p=9 | | 2z-7=2(z-13) |